The Role of Health Communication among the Poor - Syarah, Maya May; Sarwoprasodjo, Sarwititi; Lumintang, Richard W. E. (UI Scholars Hub, 2014)
Indonesia is the fifth country in the world's related TB cases. This study used the theory of ACSM (McKee 1992), a multitrack model (Tufte and Mefalopulos 2009) to analyze structural and social issues, and Health Believe Model (Rosenstock et al. 1988) to explain the behavior of the patient-level health. The research used qualitative approach with case study method of advovacy, communication and social mobilization (ACSM) of TB control program in the poor region by community TB Care 'Aisyiyah KPT West Jakarta in Kelurahan Kalianyar, Tambora, West Jakarta. A total of 18 informants as the source of data, was obtained by the snowball technique. The result shows Community TB Care 'Aisyiyah successfully gained political and social leadership acceptance in the city, district or village level that became the basis of social mobilization that generates participation by donating the treatment of citizens or economically disadvantaged groups to the poor. Credibility of cadres and treatments supporter not only shaped by good knowledge about the disease and treatment of tuberculosis acquired through training, but also the sincerity of cadres and treatment supporter as family members. It is evident that much of its claimed success has depended on interpersonal communication and the participation of volunteers, community leaders and TB drugs observer (PMO).